MODERN APPROACHES OF SECURING COMPUTER NETWORKS FROM DENIAL OF SERVICE ATTACKS - Piskozub, Andrian (International Journal of Computing, 2014)
The aim of this paper is to understand reasons why denial of service (DoS) attacks are happening; to find ways how to avoid these attacks or lessen their influence; to work out strategy of detecting and preventing these attacks.